Model Keputusan Pembelian Pakaian Batik Dan Tingkat Kepuasan Konsumen - Ernawati, Hani; Fitriana, Fitriana (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2019)
Batik is a craft that has high artistic value and has become part of Indonesia culture that must be preserved. The level of consumer satisfaction towards Batik has to be known in order to understand the market demand, as well knowing the influencing factors that have postive effect on purchasing decision of Batik. The purposes of this study are (1) measures customer satisfaction levels of batik clothing, (2) measures the influence of quality product, brand, price, and access toward purchasing decision. Method - A total of 120 respondents were asked to rate their assesment on product quality, brand, price and access to get Batik clothes and their purchasing decision. Analysis of customer satisfaction used Consumer Satisfaction Index. The relationship between quality product, brand, price, and access toward purchasing decision determined by regression analysis Ordinary Least Square. The result of this study revealed that consumers’ satisfaction toward Batik clothes included in term of satisfied category. Brand and price had positive effect on purchasing decision, but product quality and accesibity didn’t.